ANALYSIS OF THE INFLUENCE OF OPERATIONAL PARAMETERS OF THE AMINES REGENERATOR TO SUPPLY H2S THE SULFUR UNIT - Lobelles Sardiñas, Gabriel Orlando; García Conde, Luis Ernesto; Morejón Gil, Rosemary (Centro Azúcar Journal, 2022)
Introduction: In order that the amine regenerator can supply H2S to the sulfur recovery unit, it is necessary to increase the operating pressure of this tower. This process could cause operational problems, degradation or amine inventory loss, among other drawbacks. Objective: To analyze the influence of the amine regenerator operational parameters to supply H2S to the sulfur recovery unit. Materials and Methods: For the evaluation of the amine regenerator, the characteristics of the streams, products and technical specifications of the involved equipment are obtained. With these characteristics, the information flow diagram is prepared and then the simulation model is validated with respect to the design parameters of the regenerator. The CHEMCAD simulator is used, since it contains the amine thermodynamic package, necessary for the simulation of said regenerator. Results and Discussion: The pressure of the amine regenerator can vary in a range between 1.91E+005 –2.26E+005 Pa, obtaining a composition of H2S in this stream between 24.36 – 23.90 kmol/h and in the final amine stream a composition between 144.898 – 144.899 kmol/h. The temperature for this described parameters does not exceed the value of 121.7 ° C, which eliminates the possibility of degradation of the amine and therefore losses. Conclusions: It has been shown theoretically that it is possible, in this pressure range, for the acid gas stream (H2S) to enter the raw material drum of the sulfur recovery unit.